Isovitexin attenuates oxidative stress-induced skin photoaging by suppressing cellular senescence: an insight provided by transcriptomic and metabolomic - Yanpei Gu; Qing Zhu; Yumei Qin; Jianzhong Han (Journal of Agriculture and Food Research, 2025)
Aging skin has a disorganized barrier function, increasing the risk of diseases and malignant tumors. Isovitexin (Iso), a flavonoid with antioxidant, anti-cancer, neuroprotective, and lifespan-extending effects, may regulate skin photoaging, though its role is unclear. This study investigates Iso's effects on photoaging and potential mechanisms. The results showed that Iso alleviated UVB-induced photoaging in mice, improving skin hydration, increasing hydroxyproline and collagen content, suppressing epidermal thickening, and reducing MMP-1/3 expression. Further analysis indicated that Iso could significantly inhibit cellular senescence, restoring cell proliferation, reducing p16 and p21 gene and protein levels, and the percentage of SAHF positive cells. Metabolomic and transcriptomic analyzes revealed that the regulatory mechanism of Iso may be related to the PI3K-Akt signal and lipid-related metabolism. In conclusion, this study provides a scientific basis for Iso as a potential therapeutic agent against cellular senescence and photoaging. Iso has potential to develop and apply anti-aging functional foods.